Provenance and sedimentary environments of the Proterozoic São Roque Group, SE-Brazil: Contributions from petrography, geochemistry and Sm–Nd isotopic systematics of metasedimentary rocks. (November 2015) - Henrique-Pinto, R.; Janasi, V.A.; Tassinari, C.C.G.; Carvalho, B.B.; Cioffi, C.R.; Stríkis, N.M.
Abstract: The Proterozoic metasedimentary sequences exposed in the São Roque Domain (Apiaí Terrane, Ribeira Belt, southeast Brazil) consist of metasandstones and meta-felspathic wackes with some volcanic layers of within-plate geochemical signature (Boturuna Formation), a passive margin turbidite sequence of metawackes and metamudstones (Piragibu Formation), and volcano-sedimentary sequences with MORB-like basalts (Serra do Itaberaba Group; Pirapora do Bom Jesus Formation). A combination of zircon provenance studies in metasandstones, whole-rock geochemistry and Sm–Nd isotopic systematics in metamudstones was used to understand the provenance and tectonic significance of these sequences, and their implications to the evolution of the Precambrian crust in the region. Whole-rock geochemistry of metamudstones, dominantly from the Piragibu Formation, points to largely granitic sources (as indicated for instance by LREE-rich moderately fractionated REE patterns and subtle negative Eu anomalies) with some mafic contribution (responding for higher contents of Fe2 O3, MgO, V, and Cr) and were subject to moderate weathering (CIA – 51 to 85). Sm–Nd isotope data show three main peaks of Nd TDM ages at ca. 1.9, 2.1 and 2.4 Ga; the younger ages define an upper limit for the deposition of the unit, and reflect greater contributions from sources younger than the >2.1 Ga basement. The coincident age peaks of Nd TDM and U–Pb detrital zircons at 2.1–2.2 Ga and 2.4–2.5 Ga, combined with the possible presence of a small amount of zircons derived from mafic (gabbroid) sources with the same ages, as indicated by a parallel LA-ICPMS U–Pb dating study in metapsammites, are suggestive that these were major periods of crustal growth in the sources involving not only crust recycling but also some juvenile addition. A derivation from similar older Proterozoic sources deposited in a passive margin basin is consistent with the main sedimentary sequences in the São Roque Domain being broadly coeval and in part laterally continuous. The coincident age, Sm–Nd isotope signature and geographic proximity make the exposures of basement orthogneisses in the Apiaí Terrane candidates for source material to the São Roque Domain. Additional sources with younger Nd TDM could be juvenile 2.2 Ga basement from the southern portion of the São Francisco Craton and its marginal belts (e.g., Mineiro Belt and Juiz de Fora Complex). Graphical abstract: Highlights: Lithotypes with high compositional maturity are predominant. Weathering indexes indicate moderate alteration of Proterozoic sources. Geochemical behavior is consistent with deposition in passive margin basin. Main sources are granitic with minor basaltic and recycled sedimentary rocks. Sm–Nd TDM constrain deposition ages to <1.9 Ga with Paleoproterozoic and Archean sources.